2020
DOI: 10.1111/cts.12841
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Relationship of Inotuzumab Ozogamicin Exposure With Efficacy and Safety End Points in Adults With Relapsed or Refractory Acute Lymphoblastic Leukemia

Abstract: Inotuzumab ozogamicin (InO), an anti‐CD22 monoclonal antibody conjugated to calicheamicin, is approved in Europe and the United States for treatment of adults with relapsed or refractory acute lymphoblastic leukemia (ALL). Population analyses were performed to evaluate the relationship between InO exposure and efficacy and safety end points in patients with ALL. The probability of achieving complete remission/complete remission with incomplete hematologic recovery (CR/CRi) and minimal residual disease (MRD)‐ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Estimated from pediatric patients with BCP-ALL following the dosing scheme in the phase IA and phase II part of the ITCC-059 Trial, the cumulative AUC was positively associated with overall response and significantly higher among responders at the end of the first cycle. This is in agreement with the exposure-response analysis for efficacy of InO in adult patients with R/R BCP-ALL [34], where InO exposure (average concentration, as the ratio of cumulative AUC over time) is significantly and positively correlated with achieving remission and MRD negativity. There has been limited information regarding the relationship between InO exposure and clinical effectiveness in children.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Estimated from pediatric patients with BCP-ALL following the dosing scheme in the phase IA and phase II part of the ITCC-059 Trial, the cumulative AUC was positively associated with overall response and significantly higher among responders at the end of the first cycle. This is in agreement with the exposure-response analysis for efficacy of InO in adult patients with R/R BCP-ALL [34], where InO exposure (average concentration, as the ratio of cumulative AUC over time) is significantly and positively correlated with achieving remission and MRD negativity. There has been limited information regarding the relationship between InO exposure and clinical effectiveness in children.…”
Section: Discussionsupporting
confidence: 89%
“…Ergo, it was uncertain whether the InO exposure in pediatric patients with BCP-ALL following a lower dosing regimen (i.e., without a loading dose) is sufficient. A reduction in the InO dose could not only be beneficial from a pharmacoeconomic point of view but also for safety concerns, as in adults, sinusoidal obstruction syndrome was associated with a higher InO exposure [34]. At present, several trials are evaluating combinations of InO, often at a dose inferior to the RP2D of trial ITCC-059, combined with low-intensity chemotherapy and immunotherapies (e.g., blinatumomab), for example, by the MD Anderson Center and the Children's Oncology Group [50,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,13 There was a nonsignificant trend toward higher troughs in patients with CR or CRi in cycle 1, consistent with exposure-response modeling in adults where InO exposure correlated with response and MRD‐negativity. 30 Trough InO levels at cycle 2 day 1 were detectable in most patients, albeit at low levels, even in patients with significant delay from the last InO dose in cycle 1. This may affect clinical trial designs incorporating blocks of InO because of potential toxicity in subsequent chemotherapy cycles.…”
Section: Discussionmentioning
confidence: 84%
“…This model also suggested that InO PK and N-ac-gammacalicheamicin DMH release are more sensitive and useful predictors of outcomes in InO recipients than CD22 expression. Data from 243 adult patients treated with InO showed that dose exposure was significantly correlated with the achievement of both CR and MRD negativity (27). A more robust PK model was developed by using a population PK approach pooling samples from multiple adult clinical trials; both body surface area (BSA) and the baseline percentage of blasts in the peripheral blood were covariates for the time-dependent clearance components.…”
Section: Pharmacologymentioning
confidence: 99%